Subpalpebral lavage placement for remote topical administration of ocular medications in 12 dogs: A retrospective review and assessment of owner perception. (14th October 2022) - Parker, Josie; Ioannides, Joy; Kumaratunga, Vim; Preston, Juliette; Hartley, Claudia; Donaldson, David
Abstract: Objective: The aim of this study was to describe the placement of subpalpebral lavage (SPL) systems in 12 dogs (15 eyes) intolerant of topical ocular medications to assess the suitability, complications encountered and owner perception of use. Animals Studied: Retrospective review of dogs that underwent SPL placement for treatment of ocular disease at the Ophthalmology Department, University of Bristol Small Animal Hospital between 2017 and 2021. Procedure(s): Data recorded included signalment, history, diagnosis, treatment, reason for SPL placement, uni‐ or bilateral placement, duration of placement, complications, and outcome. Owner perception was assessed using an online questionnaire. Statistical analysis included McNemar and Wilcoxon signed‐ranks tests. Results: Twelve dogs (15 eyes) underwent SPL placement. Eleven owners completed the online questionnaire. Corneal ulceration was the most common disease requiring SPL placement ( n  = 13/15 eyes, 86.7%). Most cases received multimodal topical therapy ( n  = 9/15 eyes, 60.0%) via SPL. Owners administered medication 6.63 times daily via SPL (range 1–16 applications/day). All dogs requiring ongoing topical medication ( n  = 8/12, 66.7%) were trained to accept direct administration during SPL treatment. Statistically significant improvements in medication compliance, ease of application, and reduced perceived risk of iatrogenic ocular injury were reported by owners ( p ‐value = .001, .004, and .031 respectively). Minor complications were infrequently reported but an excellent outcome was achieved for all eyes. Conclusion: Subpalpebral lavage placement provides a practical and safe solution for the provision of frequent multimodal ocular medication when treating patients with a challenging temperament.